In situ growth of Sn nanoparticles confined carbon-based TiO2/TiN composite with long-term cycling stability for sodium-ion batteries. (20th January 2021) - Zhang, Yingge; Wang, Yangbo; Kong, Dezhi; Yang, Ya; Wang, Yinghui; Guo, Yan; Lu, Yang; Kim, Jang-Kyo; Luo, Yongsong
Abstract: Sn has attracted tremendous attentions in sodium ion batteries (SIBs) for its high theoretical capacity, low cost and high electronic conductivity. However, one of the critical problems to hinder the widely practical application of SIBs is the fast capacity decay during repeated charge/discharge cycles owing to the vast volume expansion and aggregation of Sn nanoparticles. Herein, the spatially confined strategy is introduced to synthesize Sn/C@TiO2 /TiN composite to address the above issues. The dual space-confined layers of carbonaceous microspheres and TiO2 could effectively buffer the volume expansion of Sn nanoparticles. Moreover, the dual conductive matrix of the inner carbon and outer TiN are favorable to enhance the electrode conductivity and accelerate Na + and electrons transfer. In addition, the first-principles simulation is further employed to investigate the electrochemical dynamics (structural deformation) of the electrode. As a result, Sn/C@TiO2 /TiN electrode exhibits a long cycle life stability (retains a capacity of 201.2 mAh/g after 500 cycles at 0.5 A/g). This spatially confined strategy might exert a profound impact on designing desirable electrode materials with long cycle life and fast redox kinetics in SIBs.